TANGGUNG JAWAB PRIBADI, KESERIUSAN KECURANGAN, RISIKO PELAPOR, DAN INTENSI WHISTLEBLOWING - Girllane Dameclelen Simatupang; Anis Chariri (Diponegoro Journal of Accounting, 2021)
This research aimed to investigate determinants of personal responsibility reporting, perceived seriousness, personal cost for reporting on whistleblowing intention. The dependent variable in this research is whistleblowing intention, while the independent variables in this research are personal responsibility of reporting, perceived seriousness, and personal cost for reporting.The sample used in this study is the financial staff at Bank Rakyat Indonesia and Bank Mandiri Kota Semarang with a total 87 respondents based on convenience sampling for sample selection. Research data is primary data with survey questionnaire methods obtained through respondents. This research examines the hypothesis by using multiple regression analysis with SPSS 23 software.The findings show that personal responsibility of reporting significantly affects whistleblowing intention. Meanwhile, perceived seriousness and personal cost for reporting are not significantly associated with whistleblowing intention.